Experimental Investigation of the Effect of a Recuperative Heat Exchanger and Throttles Opening on a CO2/Isobutane Autocascade Refrigeration System - Michał Sobieraj (Energies, 2020)
An experimental evaluation of an autocascade refrigeration (ACR) system was carried out. A zeotropic mixture of isobutane and CO2 was employed as a working fluid in an autocascade refrigeration (ACR) system. An experimental system was designed and built to study the influence of the recuperative heat exchanger (RHX) and openings of the throttle valves on the system performance. The use of RHX facilitated the condensation process and improved the cycle characteristics. The working mass concentration of CO2 was higher, as it was closer to the nominal concentration and the discharge pressure was lower by 19% to even 39% when the RHX was employed in the system. An increase of up to 20% in the coefficient of performance (COP) was observed. Furthermore, the effects of the openings of the throttle valves on the system characteristics were studied. The change in the openings of the expansion valves affected the mass flows and the working mixture composition. The working CO2 mass fraction increased with higher openings of the evaporator throttle. The subcooling degree of liquid CO2-rich refrigerant increased with higher openings of the expansion valve under the phase separator. The results of the present work should be helpful for design and optimization of autocascade systems working with natural and synthetic refrigerants.